High-fat diet impairs glucose homeostasis by increased p16 beta-cell expression and alters glucose homeostasis of the progeny in a parental-sex dependent manner - Escalona, Rene; Larqué, Carlos; Cortes, Daniela; Vilchis, Ricardo; Granados-Delgado, Emiliano; Sánchez, Abigail; Sánchez-Bringas, Guadalupe; Lugo-Martínez, Haydée (Frontiers in Endocrinology, 2023)
Obesity consists in the accumulation of adipose tissue accompanied by a low grade chronic inflammation and is considered a pandemic disease. Recent studies have observed that obesity affects females and males in a sex-dependent manner. In addition, several works have demonstrated that parental obesity increases the risk to develop obesity, insulin resistance, diabetes, and reproductive disorders. Considering that intergenerational effects of obesity may occur in a sex-dependent manner, we studied male and female Wistar rat progeny (F1) obtained from mothers or fathers (F0) fed on a high-fat diet (HFD). HFD altered body weight gain, adiposity, glucose tolerance, plasma levels of insulin and leptin, and p16 beta-cell expression. Furthermore, metabolic disturbances included impaired fasting glucose and tolerance, and hyperinsulinemia in male offspring, and at the same time reduced insulin sensitivity in female progeny.